Application of Near-Infrared Fluorescence Imaging Technology in Liver Cancer Surgery. (August 2022) - Liu, Ying; Gao, Benjian; Fang, Cheng; Su, Song; Yang, Xiaoli; Tian, Jie; Tian, Bo
Background. Hepatocellular carcinoma, among the most common malignant digestive system tumorsworldwide, is most effectively treated with precise surgical resection. Near-infrared fluorescence imaging technology is being increasingly used clinically and has achieved great initial results in the navigation of liver cancer surgery. Methods. This review describes the application of indocyanine green fluorescence (ICG) imaging technology with near-infrared window I in the navigation of liver cancer surgery, explores novel fluorescent probes and near-infrared window II fluorescence imaging technology, and discusses the development status of the 2 emerging tools. Results. ICG fluorescence imaging technology can precisely localize the tumor, reveal the boundary of liver cancer or liver segment, and identify the bile leakage. The novel fluorescent probe is more targeted than ICG, which makes the detection of cancer more accurate. Near-infrared window II fluorescence imaging technology can lead to outstanding gains in deeper detection, higher resolution, and fidelity. But, due to the shortcomings of machine and probe, it is not widely used in clinical. Conclusion. Near-infrared fluorescence imaging has great development potential. With the advent of precision medicine and the progress of various biotechnology studies, fluorescence imaging technology will be better developed and applied in the diagnosis, surgical navigation, and treatment of liver cancer.